Public Policies and Conflicts Over Water in Two Indigenous Territories in the Province of Puntarenas, Costa Rica - Mora González, Ana Lucía (Revista de historia., 2021)
This article presents a first approach to the analysis of the relationship between public policies and conflicts over water for human consumption in three communities belonging to two indigenous territories in the province of Puntarenas: the Alto Conte community in the Ngäbe Conteburica indigenous territory and the communities of Ujarrás and Guanacaste, in the indigenous territory Cabécar, Ujarrás. Based on the previous information, the work also shows the different forms of social water management present in indigenous communities in the absence of piped water system supply, as well as the internal contradictions and the ecological distribution of water in the territories that are being studied, which in turn become health risks and quality of life.